1986
DOI: 10.1118/1.595823
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the source position for the electron beams from a high‐energy linear accelerator

Abstract: We have investigated the energy and field-size dependence of the source position of the electron beams from a Varian Clinac-2,500 accelerator. Three independent experimental methods were used: (1) multipinhole camera (MPC), (2) back projection of the full width at half maximum (FWHM), and (3) the inverse square law (ISL). The positions of the virtual and effective sources were calculated using the multiple Coulomb scattering (MCS) formalism. The results obtained from the MPC agree, within the experimental unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…This method is relatively simple and requires the determination of the effective SSD for electron beams, which depends on the machine, field size, and beam energy. [212][213][214][215][216] By taking measurements at d max at various air gaps between the electron cone and water surface, a plot of the square root of I 0 / I and the gap gives a straight line with a particular slope that provides the effective SSD. Sigma-theta-͑ x ͒ is the root-mean-square value of the Gaussian projected angular distribution at the plane of the final collimating device as described by ICRU-35 ͑Ref.…”
Section: Vb3 Virtual and Effective Source Positionmentioning
confidence: 99%
“…This method is relatively simple and requires the determination of the effective SSD for electron beams, which depends on the machine, field size, and beam energy. [212][213][214][215][216] By taking measurements at d max at various air gaps between the electron cone and water surface, a plot of the square root of I 0 / I and the gap gives a straight line with a particular slope that provides the effective SSD. Sigma-theta-͑ x ͒ is the root-mean-square value of the Gaussian projected angular distribution at the plane of the final collimating device as described by ICRU-35 ͑Ref.…”
Section: Vb3 Virtual and Effective Source Positionmentioning
confidence: 99%
“…2 For machines of different design, several studies have shown that the full width at half maximum of most modern accelerator beam spots is in the range of 0.05-0.4 cm. [3][4][5][6][7] The energy cutoffs were set for all simulations to E cut = 0.521 MeV, AE = 0.521 MeV, P cut = 0.010 MeV, and AP = 0.010 MeV. The PRESTA-II algorithm ͑introduced in the EGSnrc code͒ for reduced electron step transport was used with default values in all cases to ensure correct accounting of low-energy interactions, which are important in the development of the degraded electron beam spectrum at the applicator exit, therefore having a leading role in determining the dose in the buildup region.…”
Section: Iib Monte Carlo Simulationsmentioning
confidence: 99%
“…For rectangular field sizes, it is recommended that the geometric mean of SSD eff for each side be used as the SSD eff , as this can be shown to be equivalent to the square root method of Mills et al 112 The field size dependence is caused by a lack of lateral scatter equilibrium for small apertures. 40,113 Potential dose-delivering electrons near the central axis are scattered out of the field and not fully replaced by electrons originating peripheral to the central axis. The net loss of scatter to the central axis causes the fluence to decrease with SSD more rapidly than the inverse-square law predicts.…”
Section: B2d Effectivementioning
confidence: 99%